Mental Disorders of Bangladeshi Students During the COVID-19 Pandemic: A Systematic Review - Mamun, Firoj al; Hosen, Ismail; Misti, Jannatul Mawa; Kaggwa, Mark Mohan; Mamun, Mohammed A. (Psychology Research and Behavior Management, 2021)
The unprecedented COVID-19 pandemic has become a global burden disrupting peoples’ quality of life. Students being an important cohort of a country, their mental health during this pandemic has been recognized as a concerning issue. Therefore, the prevalence and associated risk factors of Bangladeshi students’ mental health sufferings (ie, depression, anxiety, and stress) are systematically reviewed herein for the first time.Adhering to the PRISMA guideline, a systematic search was performed from 1 to 5 April, 2021 in several databases including PubMed; and finally, a total of 7 articles were included to this review.The prevalence rates of mild to severe symptoms of depression, anxiety, and stress ranged from 46.92% to 82.4%, 26.6% to 96.82%, and 28.5% to 70.1%, respectively. The risk factors concerning mental health problems included the factors related to (i) socio-demographic (younger age, gender, lower educational grade, urban residence, family size, currently living with family/parents, and having children in the family), (ii) behavior and health (smoking status, lack of physical exercise, more internet browsing time, and dissatisfaction with sleep), (iii) COVID-19 pandemic- (COVID-19 related symptoms, COVID-19 related perceptions, and fear of COVID-19 infection), (iv) miscellaneous (losing part-time teaching job, lack of study concentration, agitation, fear of getting assaulted or humiliated on the way to the hospital or home, financial problems, academic dissatisfaction, inadequate food supply, higher exposure to COVID-19 social and mass media, engaging with more recreational activities, and performing more household chores).The overall assumption of mental disorders’ prevalence rates can be regarded as problematic to this cohort. Thus, the authorities should consider setting up possible strategies to diminish the pandemic effect on students’ mental health.
Keywords: COVID-19 and psychological impact, student mental health in Bangladesh, depression, anxiety, stress, systematic review, prevalence and risk factors, pandemic in Bangladesh